Comparison of methods for estimating heights from complete stem analysis data for Pinus taeda. - Machado, Sebastião do Amaral; Silva, Luis César Rodrigues da; Figura, Marco Aurélio; Téo, Saulo Jorge; Nascimento, Rodrigo Geroni Mendes (Ciência Florestal, 2010)
The objective of this research was to compare actual heights at known ages with those estimated by the methods proposed by Graves (1906), Carmean (1972), Lenhart (1972), Newberry (1978), and the Ratio and Graphic methods, in order to identify the most accurate one for Pinus taeda from Southern Brazil. That way, six trees aged at least 11 years were used. Cross-sections with 5 cm thickness were collected at heights of 0.10 meters, 0.70 meters, 1.30 meters and so on at every 1 meter along the bole. True height growth for a given age was measured on the section itself by dividing it in two parts along the pith and looking for the exact point where the true annual height growth took place. The accuracy analyses were based on residuals between true heights and those estimated by the tested methods for each age. For this analysis, the relative mean deviation (D%), relative mean absolute deviation (AbsD%), standard deviation of differences (Sd) and sum of squared relative residuals (SSRR) were calculated. These 4 statistics evaluated together, allowed for the identification of the most accurate method for every age. Complementarily, the non paired t0.05 test for data was applied to evaluate whether the residuals from each method were significant or not. The results of the analysis indicated that Carmean (1972) and Lenhart (1972) were identical owing to the fact that they estimated the same height value for sections where there was only one growth ring finishing in the same section. This situation occurred for most of the results in this current study. It was concluded that Carmean (1972) and Lenhart (1972) were the best methods for estimating height growth because both produced non-significant residuals for the majority of the trees studied.